Contabilidade forense no Brasil: uma proposição de metodologia - Silva, Robson Maciel da (2012)
Accounting has become in recent years, a fundamental instrument for trade relations and commerce, a provider of relevant information to its users in making strategic decisions. In this interval Forensic Accounting surges and bone with the responsible for collection, preservation, restoration and analysis of evidence of financial information, presenting the facts and evidence that can be accepted in courts in triggering litigation involving corporate fraud. However, research study relating to aforementioned subject is largely unexplored and there is recognition by the academic, this fact is evidenced by the absence of reasonable amount of scientific articles, laws or professional orientation. Given this scenario, the study seeks to contribute to the elucidation and exploitation of Forensic Accounting in Brazil,identifying which are the basic procedures to perform a forensic accounting. Based on this concern, we performed a literature review on the concepts of Accounting Science, Forensic Science, Fraud, Forensic Accounting, and Criminology in the Law and Investigative Audit.Therefore, to guide this study we sought to answer the following research question: what are the basic procedures to perform a forensic accounting? Identifying the differences between the activity of expertise and forensic investigation, the relation between the formalization of forensics and procedures for joint research, and model for basic forensic accounting. The methodology applied in the study is based largely qualitative, exploratory approach. The sample was selected in a non-probabilistic, by limiting the reach of the group being studied and the small number of practitioners available to participate in the study. For this purpose, we used the "Snowball sampling" technique (snowball or reference current), where a respondent indicates another possible respondents. Finally, based on the results, Forensic Accounting could be conceptualized as a tool to support litigation in providing technical support to the judicial authorities. The study also observed that it bared a resemblance with the activities of an expert accounting, however, differing only in applicants services research, and expertise demanded by justice and forensic investigation by the executives of corporations seeking redress. Finally, the proposed forensic investigation procedures are: financial analysis, contract analysis, analysis of the relationship of payments, DuPont analysis, compliance, statistical analysis, CAAT, profiling access, electronic data recovery,investigative interview, notarial minutes, analysis of public data and physical inspection (on site).